“Believe that believe”: from Dostojevky’s Stavrogin to Gianni Vattimo - Šerpytytė, Rita (Religija ir kultūra, 2006)
The article deals with the relation between faith and nihilism in Gianni Vattimo philosophy. The position of Vattimo, treating nihilism as (hermeneutical) attempt of weak thought, is analysed. Weak thought describes itself as the attempt of thinking that approaches to the relation with the philosophical heritage of previous epochs differently and treats the very demand of overcoming (metaphysics) otherwise. The overcoming for Vattimo doesn‘t have the meaning of simple negation or transgresion already; it obtains the sense of farewal movement to metaphysics. In such perspective the search of the ontology links to nihilism, which is treated already in the positive meaning – as the last chance.